THE RELEVANCE OF THE APPLICATION OF STRUCTURAL MANAGEMENT IN UZBEKISTAN - Maxkamov Navruzjon Tukhtamishevich (Research Parks Publishers, 2020)
This article describes the importance and relevance of its use in the management of systemic management, suggests the process and mechanisms of building management methods in public administration of the Republic of Uzbekistan and becoming increasingly of systematic analysis in management, the need to apply modern management. To make the concept of a system, the importance of a systemic approach, more understandable, the article highlights a talk about a system that is specific to everyone